To break our chains : social cohesiveness and modern democracy - Braun, Jerome (Studies in critical social sciences ;, 2011)
These essays are a distillation of Jerome Brauns work in interdisciplinary social science, and especially sociology. Thus they exemplify pragmatic critical theory by dealing with culture and personality, cohesiveness and nihilism in modern societies, and the relation between community and democracy.